Do I really have to do my homework? The role of homework compliance in cognitive behavioral therapy for irritable bowel syndrome - Radziwon, Christopher D.; Quigley, Brian M.; Vargovich, Alison M.; Krasner, Susan S.; Gudleski, Gregory D.; Mason, Sarah R.; Borden, Ashlye B.; Lackner, Jeffrey M. (Behaviour research and therapy, 2022)
Treatment guidelines identify cognitive behavioral therapy (CBT) as a treatment of choice for irritable bowel syndrome (IBS). As a learning-based treatment, homework assignments are regarded as important for optimizing outcomes for CBT-treated patients. However, their actual benefit for IBS is unknown. This study examined whether homework completion corresponds with immediate and sustained treatment response in IBS patients enrolled in CBT treatment. Subjects were 358 IBS patients receiving clinic-based CBT (10 session), home-based CBT (4 session), or a 4 session, non-specific IBS education comparator as part of a large NIH trial. Homework completion was rated by clinician at each session. IBS symptom improvement was measured with the Clinician Global Improvement Scale at treatment week 5, post-treatment (week 12), and at follow-ups (weeks 22, 34, 46, 62). Homework completion rates over the 10-week acute phase corresponded with greater IBS symptom improvement and patient satisfaction at post-treatment. Early treatment homework completion did not predict early treatment response. Contrary to expectations, homework compliance rates were not greater among in-clinic session patients than home-based patients. Data lend empirical support to the clinical value of homework in teaching patients how to self-manage painful GI symptoms refractory to conventional medical and dietary therapies.